Qur'anic Study of Islamic Education - Yayat Suharyat; Idham Anshori (International Journal of Global Sustainable Research, 2023)
The Quran is the word of God delivered through the angel Gabriel to the Prophet Muhammad SAW which contains the main teachings that can be developed for the needs of all aspects of human life. In the Qur'an there are many teachings that contain principles relating to educational activities or efforts. This study uses a descriptive-analytic approach with a study of diverse literature and data sources to gain a clearer understanding of the Qur'anic Studies that are the source of Islamic Education. The results showed that the Qur'anic Study of Islamic Education continues to be relevant throughout the ages on which all elements of life depend. It is hoped that this study can contribute to efforts to instill Islamic religious education in schools that are sourced from the Qur'an and become a reference for educators and policy makers in developing an Islamic curriculum that focuses on our religious sources, namely the Qur'an.